Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine the [tex]\( y \)[/tex]-intercept of the function [tex]\( g(x) = 2 f(x) + 1 \)[/tex] where [tex]\( f(x) = e^x \)[/tex], we need to evaluate [tex]\( g(x) \)[/tex] at [tex]\( x = 0 \)[/tex].
1. Substitute [tex]\( x = 0 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(0) = e^0 \][/tex]
Since [tex]\( e^0 = 1 \)[/tex], we have:
[tex]\[ f(0) = 1 \][/tex]
2. Use the result from step 1 to evaluate [tex]\( g(x) \)[/tex] at [tex]\( x = 0 \)[/tex]:
[tex]\[ g(0) = 2 f(0) + 1 \][/tex]
Substitute [tex]\( f(0) = 1 \)[/tex]:
[tex]\[ g(0) = 2 \cdot 1 + 1 = 2 + 1 = 3 \][/tex]
Thus, the [tex]\( y \)[/tex]-intercept of the function [tex]\( g(x) \)[/tex] is [tex]\((0, 3)\)[/tex].
Therefore, the correct answer is:
D. [tex]\((0, 3)\)[/tex]
1. Substitute [tex]\( x = 0 \)[/tex] into the function [tex]\( f(x) \)[/tex]:
[tex]\[ f(0) = e^0 \][/tex]
Since [tex]\( e^0 = 1 \)[/tex], we have:
[tex]\[ f(0) = 1 \][/tex]
2. Use the result from step 1 to evaluate [tex]\( g(x) \)[/tex] at [tex]\( x = 0 \)[/tex]:
[tex]\[ g(0) = 2 f(0) + 1 \][/tex]
Substitute [tex]\( f(0) = 1 \)[/tex]:
[tex]\[ g(0) = 2 \cdot 1 + 1 = 2 + 1 = 3 \][/tex]
Thus, the [tex]\( y \)[/tex]-intercept of the function [tex]\( g(x) \)[/tex] is [tex]\((0, 3)\)[/tex].
Therefore, the correct answer is:
D. [tex]\((0, 3)\)[/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.